Status Of Apple Mosaic Virus In Kashmir Valley (Applied Biological Research, 2011)
Leaves of apple cv. ‘Red Delicious’ and ‘Golden Delicious’ were  randomly collected from commercial apple growing areas of four districts  of Jammu and Kashmir State viz., Shopian, Pulwama, Bandipora and  Kupwara for the detection of Apple mosaic virus (ApMV) by RT-PCR  technique using coat protein gene-specific primers. ApMV was present in  all the locations. RT-PCR amplified approximately 800 bp amplicons  from 30 out of 276 leaf samples thereby confirmed the infection of ApMV  in Kashmir. District Bandipora recorded highest disease incidence of  13.3% followed by Shopian (11.3%), Kupwara (10.2%) and Pulwama  (8.6%). Nineteen of the 161 cv. ‘Red Delicious’ samples and 11 of the 115  ‘Golden Delicious’ samples were found RT-PCR positive.
Keywords: Apple mosaic virus; ApMV incidence; Kashmir; RT-PCR detection